Novel bocaparvoviruses in rabbits. Issue 2 (November 2015) - Lanave, G.; Martella, V.; Farkas, S.L.; Marton, S.; Fehér, E.; Bodnar, L.; Lavazza, A.; Decaro, N.; Buonavoglia, C.; Bányai, K.
Highlights: A novel parvovirus was identified in rabbits by next generation sequencing. The virus genome displayed distinctive features of bocaparvoviruses. The virus was detected in both rabbits with enteritis and in asymptomatic animals. Sequencing of a short ORF2 region identified two main lineages/subtypes. Abstract: Bocaparvovirus is a newly established genus within the family Parvoviridae and has been identified as a possible cause of enteric, respiratory, reproductive/neonatal and neurological disease in humans and several animal species. In this study, metagenomic analysis was used to identify and characterise a novel bocaparvovirus in the faeces of rabbits with enteric disease. To assess the prevalence of the novel virus, rectal swabs and faecal samples obtained from rabbits with and without diarrhoea were screened with a specific PCR assay. The complete genome sequence of the novel parvovirus was reconstructed. The virus was distantly related to other bocaparvoviruses; the three ORFs shared 53%, 53% and 50% nucleotide identity, respectively, to homologous genes of porcine bocaparvoviruses. The virus was detected in 8/29 (28%) and 16/95 (17%) samples of rabbits with and without diarrhoea, respectively. Sequencing of the capsid protein fragment targeted by the diagnostic PCR identified two distinct bocaparvovirus populations/sub-types, with 91.7–94.5% nucleotide identity to each other. Including these novel parvoviruses in diagnostic algorithms of rabbit diseases might help inform their potential pathogenic role and impact on rabbit production and the virological profiles of laboratory rabbits.